Teachers and students response toward the dissolution of the international standard school pilot project (RSBI) at vocational schools in Bantul: A case study - Triyono Triyono; Nanik Supriani (Journal of English Language and Pedagogy, 2018)
This study aims to research the responses of teachers and students against the dissolution of RSBI at Vocational Schools in Bantul. The research questions are what are the students and the teachersâ€™ responses toward the dissolution of RSBI. This research is a descriptive qualitative research and the approach was naturalistic. The research settings were SMKN I Bantul and SMKN 1 Kasihan Bantul. The data was collected through an open questionnaire. It was analyzed by categorizing the data using a continuous comparison technique. The key instrument of this research was the researcher himself. TheÂ  research finding of the research related to the responses were that (1) teachers become more creative in improving their teaching methods (2) the burden of teachers psychology in teaching is reduced (3) the teachers are more comfortable in teaching (4) using Indonesian in learning process can improve a sense of nationalism (5) there was loss of discrimination against individual, social and school (6) the ability of students in English language is declined (7) student facilities are stunted (8) there is lack of opportunity to access information and learning technology ( 8) there is elimination of financial support from government (9) the opportunity for joining on teacher training is limited (10) opportunity for getting qualified students is decreased (11) some school programs are deleted.